Sofðu Unga Ástin Mín: The Archaeology of Emotion in Child Burials at Skriðuklaustur Monastery - Daníel Freyr Ívarsson 1996- (2024)
The archaeology of children and childhood has historically been marginalized in archaeological research, with increased attention emerging only in the 1980s due to the rise of gender archaeology and feminist theory. However, there is a notable research gap in the study of medieval burials of infants and children in Iceland, particularly concerning the emotions associated with these burials. This thesis explores the possibility of revealing emotions in the mortuary rituals of children buried in Skriðuklaustur Cemetery. Drawing on interdisciplinary material from archaeologists, sociologists, psychologists, and historians, as well as data collected during excavations at Skriðuklaustur between the years 2002 and 2012, the thesis aims to shed light not only on the study of children and childhood but also on emotions and traces of grief in burial contexts in Icelandic archaeology. The results may contribute to a deeper understanding of the cultural and emotional aspects of child burials in Iceland and create a broader discussion in the field, hopefully leading to further research on this topic.